2015
DOI: 10.1097/prs.0000000000001487
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Outcomes after Revision Amputation for Treatment of Traumatic Finger Amputation

Abstract: Background Revision amputations are often the treatment for traumatic finger amputation injuries. However, patient outcomes are inadequately reported, and their impact poorly understood. We performed a systematic review to evaluate outcomes of revision amputations and amputation wound coverage techniques. Methods We searched all available English literature in PubMed and EMBASE for articles reporting outcomes of non-replantation treatments for traumatic finger amputation injuries, including revision amputati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 67 publications
(88 reference statements)
0
20
0
Order By: Relevance
“…The loss of any digit has functional, aesthetic, and psychological sequelae [21115]. In circumstances where digital reconstruction is anticipated, autologous reconstruction should be considered the gold standard [2312].…”
Section: Discussionmentioning
confidence: 99%
“…The loss of any digit has functional, aesthetic, and psychological sequelae [21115]. In circumstances where digital reconstruction is anticipated, autologous reconstruction should be considered the gold standard [2312].…”
Section: Discussionmentioning
confidence: 99%
“…Closure can be performed directly with or without revision amputation/bone shortening by using local skin flaps or tissue grafting (sometimes with the amputated part itself). A systematic review by Yuan et al showed that 91% of patients undergoing revision amputation with or without local flaps were satisfied with their result and maintained an acceptable range of motion [62]. However, the closure of skin flaps has been shown to inhibit the regenerative response.…”
Section: Current Clinical Approaches To Digit Tip and Upper Extremmentioning
confidence: 99%
“…It can achieve almost normal sensibility and satisfactory motion [6]. However, it also has many disadvantages, such as frequent cold intolerance [7], painful neuroma formation [8], shortening of the ngers and poor appearance. It cannot be accepted by many Asians especially female patients.…”
Section: Discussionmentioning
confidence: 99%
“…The ap repair can ensure that the nger will not shorten, but there are also many kinds of drawbacks such as poor appearance, large damage, poor sensitivity [7] and poor mechanical properties of the ap.…”
Section: Discussionmentioning
confidence: 99%